If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -16 = 9x Reorder the terms: -16 + X = 9x Solving -16 + X = 9x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + X = 16 + 9x Combine like terms: -16 + 16 = 0 0 + X = 16 + 9x X = 16 + 9x Simplifying X = 16 + 9x
| 26x^2+120x+150=8x^2 | | 8(3x-1)=4(6x+2) | | 0.3-0.7x+2=-8 | | 2=4(x-4)-(x-9) | | 5=-p-12 | | 2(v-1)+4=14 | | 7x+2=x+14 | | 2+3[1+2(4+1)]= | | 6(-y+4)-3(2y-3)=-y+5+5y | | 5p-26=18p | | (c+4)3-6c=2(4-2c) | | 7x+5=-51 | | Hyits=a | | 6m=60 | | 24-2[5-(3*1)]= | | 3=5+3t | | 2x-8=12+3x | | 4x+18-6x+38= | | 0=2t^2-13t+21 | | k+5=4k-10 | | -2x+4=-14 | | (5x^2-7x+7)*(6x+9)=0 | | Y+5=4y-10 | | 7+2s-6=6s+8-3s | | 9x^2-34x-8=0 | | 13t-48=2+14t | | 5-2x=-5 | | 3z+15=27 | | 16x^2-320=88x | | 4x-8=12+3x | | 4x^2-2x-9=7x+8 | | 2(4x-3)-=4+2x |